Genome-Based Classification of Strain 16-SW-7, a Marine Bacterium Capable of Converting B Red Blood Cells, as Pseudoalteromonas distincta and Proposal to Reclassify Pseudoalteromonas paragorgicola as a Later Heterotypic Synonym of Pseudoalteromonas distincta - Nedashkovkaya, Olga I.; Kim, Song-Gun; Balabanova, Larissa A.; Zhukova, Natalia V.; Son, Oksana M.; Tekutyeva, Liudmila A.; Mikhailov, Valery V. (Frontiers in Microbiology, 2022)
A strictly aerobic, Gram-stain-negative, rod-shaped and motile bacterium, designated strain 16-SW-7, isolated from a seawater sample, was investigated in details due to its ability to produce a unique α-galactosidase converting B red blood cells into the universal type blood cells. The phylogenetic analysis based on 16S rRNA gene sequences revealed that the strain 16-SW-7 is a member of the gammaproteobacteria genus Pseudoalteromonas. The most closely relatives of the environmental isolate were Pseudoalteromonas distincta KMM 638T and Pseudoalteromonas paragorgicola KMM 3548T, with the plural paralogous 16S rRNA genes of 99.87%-100% similarity. The strain 16-SW-7 grew with 1-10% NaCl and at 4-34 C, and hydrolyzed casein, gelatin, tyrosine and DNA. The genomic DNA G + C content was 39.3 mol%. The prevalent fatty acids were C16:1 7c, C16:0, C17:1 8c, C18:1 7c, C17:0 and C12:0 3-OH. The polar lipid profile was characterized by the presence of phosphatidylethanolamine, phosphatidylglycerol, two unidentified amino lipids and three unidentified lipids. The major respiratory quinone was Q-8. The finished genome of the strain 16-SW-7 (GenBank assembly accession number: GCA_005877035.1) has a size of 4,531,445 bp and comprises two circular chromosomes L1 and S1, deposited in the GenBank under the accession numbers CP040558 and CP040559, respectively. The strain 16-SW-7 has the ANI values of 98.2% with KMM 638T and KMM 3548T and the DDH values of 84.4 and 83.5%, respectively, indicating clearly that the three strains belonged to a single species. According to phylogenetic evidence and similarity for the chemotaxonomic and genotypic properties, the strain 16-SW-7 (=KCTC 52772 = KMM 701) represents a novel member of the species Pseudoalteromonas distincta. Also, we have proposed to reclassify Pseudoalteromonas paragorgicola as a later heterotypic synonym of P. distincta based on the rules of priority with the emendation of the species.